The brain in flow: A systematic review on the neural basis of the flow state - Alameda, Clara; Sanabria, Daniel; Ciria, Luis F. (Cortex, 2022)
Flow state is a subjective experience that people report when task performance is experienced as automatic, intrinsically rewarding, optimal and effortless. While this intriguing phenomenon is the subject of a plethora of behavioural studies, only recently researchers have started to look at its neural correlates. Here, we aim to systematically and critically review the existing literature on the neural correlates of the flow state. Three electronic databases (Web of Science, Scopus and PsycINFO) were searched to acquire information on eligible articles in July, 2021, and updated in March, 2022. Studies that measured or manipulated flow state (through questionnaires or employing experimental paradigms) and recorded associated brain activity with electroencephalography (EEG), functional magnetic resonance (fMRI) or functional near-infrared spectroscopy (fNIRS) or manipulated brain activity with transcranial direct current stimulation (tDCS) were selected. We used the Cochrane Collaboration Risk of Bias 2 (RoB 2) tool to assess the methodological quality of eligible records. In total, 25 studies were included, which involved 471 participants. In general, the studies that experimentally addressed flow state and its neural dynamics seem to converge on the key role of structures linked to attention, executive function and reward systems, giving to the anterior brain areas (e.g., the DLPC, MPFC, IFG) a crucial role in the experience of flow. However, the dynamics of these brain regions during flow state are inconsistent across studies. In light of the results, we conclude that the current available evidence is sparse and inconclusive, which limits any theoretical debate. We also outline major limitations of this literature (the small number of studies, the high heterogeneity across them and their important methodological constraints) and highlight several aspects regarding experimental design and flow measurements that may provide useful avenues for future studies on this topic.